The love motion in a minor piano concerto op. 54 and variations on the theme by R. Schumann op. 20 - Yang Yang (2016)
This thesis aims to research the role of music as an emotion expressed in motion. Based on the study of two pieces: Robert Schumann’s A minor Piano Concerto Op.54 and Clara Schumann’s Variations on a theme by Robert Schumann Op. 20, I explore the emotion of love between Robert and Clara Schumann throughout their lives, verifying the emotion of love as related to their musical creativity. Another important aim of this thesis involves my interpretation and playing experience of these two compositions. I obtain my understanding of the musical moods and meaning enriching my imagination, which translates through the aural senses to the kinetic body movements, culminating in the real musical sound and its emotional expression.